Inclusive Britishness: A Multiculturalist Advance. (30th October 2012) - Uberoi, Varun; Modood, Tariq
Abstract : Scholars argue that policies of multiculturalism in different countries are in retreat or in question. Britain is often used as an example of this, and leading British politicians and commentators often criticise such a policy. Yet a long‐held multiculturalist goal has been to make Britishness more inclusive and this is something leading politicians were until recently uncommitted to. We use interviews with politicians who have served in this government and the last, the measures they have introduced, their media contributions, speeches and policy documents, to show that they are now committed to this goal. At a time when a British policy of multiculturalism is said to be in retreat or in question we identify a multiculturalist advance and show that this raises a range of difficult questions about government approaches to 'Britishness'.